Effect of die design parameters on the deformation behavior in pure shear extrusion. (15th October 2015) - Rahimi, F.; Eivani, A.R.; Kiani, M.
Graphical abstract: Highlights: Underfilling and strain inhomogeneity occur during pure shear extrusion. Underfilling reduces with increasing diameter ratio. Strain increases with increasing diameter ratio and reducing length of the deformation zone. Inhomogeneity increases with increasing diameter ratio and shortening deformation zone. Abstract: Influences of die design parameters in terms of diameter ratio and length of the deformation zone on the distribution of effective strain, filling fraction of the die exit channel and pressing load in pure shear extrusion (PSE) are studied using finite element method (FEM). Dimensional stability, pressing load and hardness measurements are used to validate the predictions of the simulation. Acceptable agreements between the predictions of simulation and experimental results are observed. It is found that strain is inhomogeneously distributed which increases from the center to the corners. Effective strain, inhomogeneity of strain, filling fraction of the die exit channel and pressing load are increased with increasing diameter ratio. In addition, the work-piece is deformed more homogeneously at lower pressing load by increasing the length of deformation zone. However, filling fraction of the die exit channel initially increases by the length of the deformation zone up to 60 mm after which it reduces. The optimum die design parameters covering a range of acceptable effective strain and strain homogeneity, filling fraction of the die exit channel and pressing load are proposed as being 60 mm and 2 for length of the deformation zone and diameter ratio, respectively.